Ocorrência de anticorpos contra Leishmania spp., Neospora caninum e Toxoplasma gondii em soros de cães atendidos no Hospital Veterinário da Universidade Estadual de Londrina-Pr - Zulpo, Dauton Luiz; De Carvalho Leite, João Henrique Artero [UNESP]; Da Cunha, Ivo Alexandre Leme; De Barros, Luis Daniel; Taroda, Alessandra; Júnior, Valdair Elemar Camargo; Dos Santos, Hanna Lia Ettiene Peruch Lemos; Garcia, João Luis (Universidade Estadual de Londrina, 2012)
The aim of this study was to detect the presence of IgG antibodies anti-Leishmania spp., Toxoplasma gondii and Neospora caninum in dogs from a Veterinary Hospital from Universidade Estadual de Londrina. Blood samples from 112 animals were obtained by jugular venipuncture to obtain sera. The samples were tested by indirect immunofluorescence to detect antibodies anti-Leishmania spp., anti-N. caninum and anti-T. gondii. Thirteen (11.61%), 25 (22.32%), and 57 (50.89%) samples were positive for Leishmania spp., N. caninum, and T. gondii, respectively. The co-presence of anti-Leishmania spp. and N. caninum was observed in 6 (5.36%), anti-Leishmania spp. and anti-T. gondii in 8 (14.7%), and anti-N. caninum and anti-T. gondii in 18 (16.07%) samples. The co-presence of anti-Leishmania spp., anti-N. caninum and anti-T. gondii was observed in 5 (4.46%) dogs. There was a higher prevalence of Leishmania in Toxoplasma and Neospora positive animals, however, these results were not statistically significant (range p = 0.052 p = 0.06). The dogs have an important role in the epidemiological cycle of these diseases, which are important in animal and public health. The northern state of Paraná is an endemic area for human cutaneous leishmaniasis, therefore, studies should be conducted to uncover the real role of dogs as reservoirs of Leishmania to humans in the state.
Occurrence of anti-Leishmania spp., Neospora caninum and Toxoplasma gondii antibodies in dog sera from Veterinary Hospital from Universidade Estadual de Londrina
Keywords: Leishmaniasis; Neosporosis and dog population hospital; Serological reaction; Toxoplasmosis